Mild Malnutrition Contributes the Greatest to the Poor Prognosis in Coronary Artery Disease With Well-Controlled Low-Density Lipoprotein Cholesterol Levels: A 4,863 Chinese Cohort Study - Wang, Bo; Guo, Zhaodong; Liu, Jin; Li, Huanqiang; Mai, Ziling; Lin, Feng; Ying, Ming; Yu, Yaren; Chen, Shiqun; Li, Qiang; Huang, Haozhang; Wei, Wen; et al. (Frontiers in Nutrition, 2021)
Background: Previous studies reported that patients with coronary artery disease (CAD) and well-controlled baseline LDL-C (< 1.8mmol/L) still had higher long-term all-cause mortality. However, no study has been conducted to explore the independent risk factors for long-term mortality. In addition, there also was no study evaluating the population attributable risk (PAR) of independent risk factors in combination with their prevalence and relative risk. Therefore, we aimed to identify the independent risk factors and estimate their PAR in patients with CAD and well-controlled baseline LDL-C (< 1.8mmol/L). Methods: We analyzed 4,863 consecutive CAD patients with well-controlled baseline LDL-C admitted to Guangdong Provincial People’s Hospital in China from January 2007 to December 2018. Independent risk factors for long-term all-cause death were evaluated through stepwise approach and multivariable Cox regression analysis. PAR of independent risk factors was calculated with their hazard ratio and prevalence among our cohort. Results: The overall mortality was 16.00% (n = 778) over a median follow-up period of 5.93 years. Independent risk factors for all-cause death included malnutrition, age ≥ 75 years, congestive heart failure (CHF), chronic kidney disease (CKD) and atrial fibrillation. Among these risk factors of interest, the hazard ratio (HR) of severe malnutrition was the highest (HR 2.82, 95% CI: 1.86-4.26), and the PAR of mild malnutrition was the highest (19.49%, 95% CI: 0.65-36.01%). Conclusion: Malnutrition, age ≥ 75 years, CHF, CKD and atrial fibrillation were independent predictors for long-term all-cause mortality in CAD patients with well-controlled LDL-C levels. Considering prevalence of these risk factors, more attention should be paid to the occurrence of mild malnutrition for these patients.